THE STAGES, COMPARISONS AND FACTORS OF FIRST LANGUAGE ACQUISITION OF TWO-YEARS-OLD MALE AND FEMALE CHILD - Julisah Izar; Muhammad Muslim Nasution; Putri Wahyu Ilahi (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2020)
This study aimed to discuss the stages, comparisons, and factors of first language acquisition of male and female children of age 2 years old through utterances spoken in phonological, morphological and syntactic stages. This type of research used qualitative methods and descriptive approaches. The objects of this research were male child with initial (AM) and female child with initial (FA) and they are two years old The data of this study were taken from field observations published in the video and analyzed according to phonological, morphological and syntactic stages and then proceed with a comparative analysis of the mechanisms and factors for language acquisition. The results of this study showed that in the stages of language acqusition male child with initial (AM) was superior then female child with initial (FA) in the phonological, morphological, syntactic, in the comparisons stage male child with initial (AM) tended to imitate what his mother uttered while female child with initial (FA) was kind of observing and in the factors oh the language acquisition both of child between male and female were cused by different social interaction factor.